PENERAPAN PRINSIP-PRINSIP ANDRAGOGI DALAM PENDIDIKAN DAN PELATIHAN: EVALUASI DENGAN STAKE’S RESPONSIVE MODEL - MANSUR MANSUR (Jurnal Evaluasi Pendidikan, 2013)
The aim of this research is to obtain an objective and comprehensive pictures about the results of applying the andragogical principles in the implementation of education and training. This research used evaluation research method with Stake’s Responsive Evaluation Model. The subject of this research is the training participants, training committees, facilitators, teacher trainers, and the training program supervisor. The data were collected through interview techniques, focus group discussion, observation, questionnaire, and document study. The results of this research showed that some of the component has met the criteria in the implementation of the program, but most of the component and other training aspects require further development. The fundamental weaknesses of the training implementations were inadequate understanding of the conceptual of the facilitator’s to the adult learning principles. This implications for the whole training process and results achieved. However, the summary comes up to a conclusion that the implementation training at Educational Quality Assurance Institution of Maluku Province still need improvement, especially the aspect of application of adult learning principles.